Telehealth after one year of Breast Cancer Surgery as a Physical Therapy Follow-up Strategy - Casagrande, Josélia Fiorin; Macedo, Flávia Oliveira; Fabro, Erica Alves Nogueira; Ferreira, Flávia Orind; Torres, Daniele Medeiros; de Oliveira, Juliana Flávia de Oliveira Tavares; Saraiva, Simone Abrantes; Costa, Rejane Medeiros (Mastology, 2025)
Breast cancer is the most prevalent type of invasive cancer in the female population. The surgical procedure is one of the aspects of oncological treatment. However, there are several postoperative complications resulting from this process, in which physical therapists work from prevention to treatment. During the COVID-19 pandemic, the physical therapy service implemented teleconsultations for the six-month and one-year postoperative follow-ups. The purpose of this article was to evaluate the prevalence of complications identified in physical therapy follow-up, through teleconsultation, and to describe the frequency of face-to-face evaluations to confirm the physical therapy diagnosis. Methods: This is a cross-sectional study, including patients submitted to surgical treatment of breast cancer, from January 2019 to September 2021, and who were seen at the one-year postoperative teleconsultation. Results: We included 362 patients, with a mean age of 58.17 (±12.16) years. Among the reported complications, the most frequent was paresthesia in the intercostobrachial nerve (87.1%); 23.8% of the patients reported pain; and 22.1%, phantom breast sensation. 11.9% (n=43) of the patients were referred for face-to-face evaluation, being 58.1% (n=25) due to the perception of lymphedema as the main reason for these referrals. Conclusions: The most frequent complications reported by patients in one-year teleconsultation were paresthesia, followed by pain and sensation of phantom breast. The greatest reason for referrals to face-to-face consultation was lymphedema. With such findings, this modality of care shows a possibility of effective follow-up in the postoperative period of breast cancer.